STUDY OF MODIFIED RECOMBINANT APOLIPOPROTEIN A-I AS A CARRIER OF SMALL INTERFERRING RNA - A. V. Ryabchenko; M. V. Kotova; R. A. Knyazev; N. V. Trifonova; L. M. Polyakov (Сибирский научный медицинский журнал, 2019)
With the widespread development of the phenomenon of RNA interference, currently, researchers are puzzled to obtain effective carriers of small interfering RNA (siRNA). Previously, we obtained a modified recombinant polypeptide based on human apolipoprotein A-1 (apoA-I), capable of binding to plasmid DNA. The aim of the investigation was to study the possibilities of modified recombinant proteins of apolipoprotein A-I to transfer siRNA into tumor cells. Material and methods. The studies were performed on a model of transformed macrophages of mice RAW 264.7 that stably expressed the green fluorescent protein (GFP) gene (line of clone 8A3). Recombinant pro-apo A-I, its modified analog, carrying at the C-terminus of 10 amino acid residues of lysine (apo AK10), and Lipofectamine 2000 transfection reagent were studied as siRNA carriers. Proteins were obtained from the corresponding E. coli producer strains. The transfer object was a siRNA duplex, in which one nucleotide was complementary to the matrix RNA of GFP gene. Cell fluorescence was measured on the second day using a fluorescent plate analyzer. Results and discussion. The results of the study showed that proteins pro-apoA and apoAK10 labeled with fluorescein isothiocyanate penetrate the RAW 264.7 cells. The results of the study RNA interference showed that the incubation of cells with a mixture of miRNA and Lipofectamine 2000 caused a decrease in the fluorescence of the 8A3 cell lines, which indicates a correct selection of siRNA to the matrix RNA of the gfp gene. However, when 8A3 cells were incubated with a mixture of miRNA and recombinant pro-apo A-I and apo AK10, a decrease in fluorescence relative to the control cells incubated only with miRNA was not observed. Conclusion. It was shown that both the recombinant protein pro-apo A-I and the modified apoAK10 penetrate the transformed mouse macrophages of the line RAW264.7, but do not promote RNA interference in these cells.